An appraisal of the China’s claims in the South China Sea territorial disputes - Ahmad, Muhamad Hassan; Ali Mohamed, Ashgar Ali; Eishan Jan, Mohammad Naqib (USA Passion Development Sdn. Bhd., 2018)
Competing territorial and boundary claims over the various maritime features in the South China Sea among the disputing parties, namely, Brunei, China, Malaysia, Taiwan, the Philippines and Vietnam have been one of the most contentious issues for some decades. China claims almost 90 percent of the South China Sea by arguing that both maritime and land territories in the region were regarded as integral parts of the Chinese nation since centuries ago. In the same vein, other disputing parties also made numerous claims to their respective contiguous parts of the South China Sea. Despite the fact that these nations have been trying to resolve the disputes, tensions among the rival countries have steadily increased. This study is primarily doctrinal and qualitative in nature. The paper greatly contributes to evaluate Chinese territorial claims in resolving the South China Sea territorial disputes. The authors propose that China has to acquire the sovereignty over land territories in the South China Sea in conformity with the modes of acquisition of state territory under contemporary international law. Then, it can claim maritime boundaries on the basis of the land territory in accordance with the relevant provisions under the United Nations Convention on the Law of the Sea 1982 (UNCLOS 1982). It is further suggested that the adjudicative settlement either before the International Court of Justice (ICJ), the International Tribunal for the Law of the Sea (ITLOS) or an ad hoc international territorial arbitration would be desirable between or among the parties to deliberate further on the disputes with the view to maintain the international peace and security.